Congenital Myasthenic Syndromes: End-Plate AChR Lack - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Two families with 5 affected members suffering from congenital myasthenic syndrome are reported from University Hospital, Bonn, Germany.